Analisis Sistem Akad Sewa Menyewa Tambak Garam Di Desa Marengan - Aisyah (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2021)
Madura as the largest salt producing island in Indonesia and even in Southeast Asia, is an island that is included in the province of East Java. Madura Island consists of 4 regencies, and Sumenep Regency is the largest salt producer compared to 3 other regencies. So it is not surprising that the Head Office of PT. Garam is located in Sumenep, more precisely in Kalianget District. Marengan Village, Kaleangat Subdistrict, is the largest salt contributor village in Semenep Regency, where the majority of Marengan people are salt farmers in meeting their daily needs. All kinds of businesses run by someone do not escape the ijarah contract (lease), the application of the ijarah contract by salt farmers in the Marengan village is an agreement between the owner of the bailout and the salt farmer with the aim of mutually benefiting. This journal specifically provides information in the form of an understanding of the salt pond ijarah contract system in the village of Marengan, with a descriptive analysis method, by describing in detail the meaning of ijarah, the ijarah system, the application of ijarah, the terms of ijrah, the pillars of ijrah, the cancellation of ijarah and the impact of the contract. ijarah to both parties.